Data Structures and Program Design in C / Second Edition - Kruse L. Robert; Leung P. Bruce; Tondo L. Clovis (Prentice Hall, 1997)
This book emphasizes problem specification and program design, analysis, testing, verification, and program correctness. Preface, Programming Principles, Introduction to Software Engineering, Stacks and Recursion, Queues and Linked Lists, General Lists, Searching, Sorting, Tables and Information Retrieval, Binary Trees, Multiway Trees, Graphs, References for Further Reading, Index.